Amplifying Feminism through the Empowerment Program Kartini Corner: A Gender Mainstreaming Endeavour in Rural Indonesia - Listiani, Herlina Dedy; Sukesi, Keppi; Wike, Wike (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2025)
Limited access and a strong patriarchal culture in rural Indonesia remain efficacious factors that limit women's choices and participation in the public domain. The reality of gender injustice many women experience has been at the heart of feminist struggles since the 19th century. With a qualitative approach, this study aims to identify and analyze feminist values implemented by the "Kartini Corner" program in Kendalrejo Village, Pemalang Regency (Central Java). Data collected through documentation and literature studies were analyzed using Nancy Fraser's feminist framework: recognition, redistribution, collective action (solidarity), and women's empowerment. The study demonstrates that "Kartini Corner" was able to facilitate women's aspirations and participation through their active and meaningful involvement both as participants and committee members. The series of activities in this program manifested the strategy of implementing gender mainstreaming, which in this case was integrated with the Sustainable Village Development Goals (SDGs Desa). This study makes a significant contribution to the contextual feminist discourse in rural Indonesia by presenting an analysis based on Nancy Fraser’s feminist theory within a local community program. In addition, the research provides empirical evidence that local initiatives such as Kartini Corner can serve as a means of social transformation that empowers rural women to actively participate in the public sphere.